2018
DOI: 10.1002/ece3.4502
|View full text |Cite
|
Sign up to set email alerts
|

Social density, but not sex ratio, drives ecdysteroid hormone provisioning to eggs by female house crickets (Acheta domesticus)

Abstract: Social environment profoundly influences the fitness of animals, affecting their probability of survival to adulthood, longevity, and reproductive output. The social conditions experienced by parents at the time of reproduction can predict the social environments that offspring will face. Despite clear challenges in predicting future environmental conditions, adaptive maternal effects provide a mechanism of passing environmental information from parent to offspring and are now considered pervasive in natural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
(111 reference statements)
0
12
0
1
Order By: Relevance
“…Considered separately, nutritional imbalance alone negatively affects a plethora of biological phenomena, for instance, development and reproduction [1][2][3][4], and additionally can induce long-lasting behavioural changes [5][6][7]. Likewise, the social environment bears the capacity to change gene expression patterns [8] and phenotype [9][10][11] in non-social animals. The combined effects of population density and food availability have been addressed in several studies [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Considered separately, nutritional imbalance alone negatively affects a plethora of biological phenomena, for instance, development and reproduction [1][2][3][4], and additionally can induce long-lasting behavioural changes [5][6][7]. Likewise, the social environment bears the capacity to change gene expression patterns [8] and phenotype [9][10][11] in non-social animals. The combined effects of population density and food availability have been addressed in several studies [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Density-dependent maternal effects have been reported mainly in avian systems, where mothers adapt androgen allocation to the current social density (Remeš et al 2011, Mazuc et al 2003. Recently, similar effects of population density have been recorded in crickets, where females adjusted hormonal levels of their eggs to the experienced social environment (Crocker and Hunter 2018). Also, in mammals, population density was shown to alter maternal investment and increase offspring growth at high population densities to increase the probability of surviving winter periods.…”
Section: Early Life Population Density and Sex-specific Effects Of Mamentioning
confidence: 82%
“…Acheta domesticus, differential expression, house cricket, IDA, liquid chromatography, multifactorial experiment, nutritional ecology, SWATH, tandem mass spectrometry In a recent study (Gutiérrez, Fresch, et al, 2020), we subjected the house cricket A. domesticus to a factorial experiment where diet composition and social environment were manipulated. Such experimental factors are considered largely influential on the survival, development, and fitness of animals (Clark et al, 2015;Crocker & Hunter, 2018;Dávila & Aron, 2017;Han & Dingemanse, 2017;Swift et al, 1996). We showed that A. domesticus exhibited considerable sex-specific differences to disparate rearing conditions.…”
Section: Introductionmentioning
confidence: 84%